Fermentation Characteristics (In Vitro) of Palm Oil Trunk Waste as Feed for Lactating Dairy Cow: Kajian in vitro limbah batang kelapa sawit sebagai pakan ternak sapi perah - Shilvia, S; Permana, Idat Galih; Evvyernie, D; R, A (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2023)
This study aimed to evaluate the applicability of palm oil trunk waste utilization as a feed source for lactating dairy cows using an in vitro approach. This study used a randomized complete block design with 4 treatments and 3 groups. Treatment consisted of P0 (control diet), P1 (control diet supplemented with 12.5% palm oil trunk), P2 (control diet supplemented with 25% palm oil trunk), P3 (control diet with commercial concentrate). The parameters observed were rumen pH, NH3 concentration, total VFA concentration, and in vitro dry matter and organic matter digestibility (IVDMD and IVOMD) coefficients. The findings of this study showed a significant 41.73% in NH3 concentration, 24.96% in total VFA concentration, 10.47% in IVDMD, and 10.91% in IVOMD, upon introducing 25% palm oil trunk waste into the ration (p<0.05), except for rumen pH. It can be concluded that palm oil trunk waste can be used at a level of up to 25% in the diet of lactating dairy cows. Keywords: digestibility, fermentation, in vitro, palm oil trunk, unconventional feed